Cytokine profile in human eyes: contribution of a new cytokine combination for differential diagnosis between intraocular lymphoma or uveitis. - Sylvain Fisson (Public Library of Science (PLoS), 2013)
Primary intraocular lymphoma (PIOL), also called primary vitreoretinal lymphomas, often masquerades as uveitis. This misdiagnosis can result in subsequent brain involvement and oculocerebral lymphoma (OCL). In this study, we sought to characterize the helper T-cell type 1 (Th1)/Th2 cytokine profile in vitreous samples from patients with PIOL, OCL, uveitis and controls with non-inflammatory disease. Vitreous and aqueous humor samples from 87 patients with PIOL (n = 30), OCL (n = 12), uveitis (n = 34), and retinal detachment (RD) without hemorrhage (n = 11) were analyzed and their concentrations of interleukin (IL)-2, IL-4, IL-6, IL-10, interferon (IFN)-γ, and tumor necrosis factor (TNF)-α were determined by flow cytometric bead arrays (CBA). The IL-10 levels determined by CBA were compared with those by ELISA. IL-10 concentrations measured by CBA and ELISA were highly correlated. IL-2, IL-4, and TNFα were not detected in any sample. The only cytokine detected at a significant level in samples from RD vitreous was IL-6. The IL-10/IL-6 ratio, as previously reported, was slightly higher in PIOL than in uveitis samples, but not for all patients. Cytokine profiles from PIOL and OCL samples did not differ. The combination of the IL-10/IL-6 and IL-10/IFNγ ratios was highly informative for discriminating PIOL/OCL from uveitis samples and for therapeutic follow up of PIOL. This strategy might be very helpful as an initial screening to rule out PIOL in patients thought to have uveitis.